PENERAPAN MODEL PEMBELAJARAN TALKING STICK TERHADAP PENINGKATAN PEMAHAMAN ISI CERITA PADA SISWA SEKOLAH DASAR - Putri, Meiliani; Yandri Kusuma, Yanti; Fauziddin; Yusnira; Syahrul Rizal, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the increase in understanding of story content through the application of the talking stick learning model in Grade IV Students of UPT SDN 007 Pulau Tingg. This research is motivated by the low understanding of the content of the story of students in the learning process in the Indonesian subject in grade IV. This study is a Classroom Action Research (CAR), which is carried out in two cycles and each cycle consists of two meetings. The subjects in this study are 1 teacher and 20 grade IV students of SDN 007 Pulau Tinggi. While the object is the application of talking stick learning and the ability to understand the content of the story in students. Data collection techniques use observation, testing, and documentation techniques. While the data analysis technique used is qualitative descriptive analysis with percentages. Based on the results of research and data analysis, it shows that the talking stick learning model can improve students' ability to understand the content of the story. This can be seen from before the action, the average understanding of the content of the story of students only reached 62.25 and was in the sufficient category. Then after applying the talking stick learning model in cycle I, the average ability to understand the content of the story of students increased to 71.0 and was in the sufficient category. In cycle II, the average ability to understand the content of the story of students increased, reaching 85.25 or was in the good category. Thus, it can be concluded that the talking stick learning model can improve students' ability to understand the content of the story in the Indonesian subject of grade IV SDN 007 Pulau Tinggi.